PENGARUH POLIMER KITOSAN DAN POLIVINIL ALKOHOL TAUT SILANG NATRIUM TRIPOLI FOSFAT TERHADAP KARAKTER PENETRASI FILM NATRIUM DIKLOFENAK - Ernawaty Ginting; Robiatun Rambe (JIFI (Jurnal Ilmiah Farmasi Imelda), 2020)
Background: Diclofenac sodium is a non-steroidal anti-inflammatory drug which has anti-inflammatory and pain effects. Transdermal administration of diclofenac sodium can control the release of diclofenac sodium from its base, which is expected to avoid side effects in the stomach and first pass metabolism in the liver. Objective: This study aims to determine the effect of chitosan polymers and polyvinyl alcohol crosslinked sodium tripoli phosphate on the penetration character of diclofenac sodium film. Method: Transdermal film is made by mixing chitosan solution and polyvinyl alcohol solution with the addition of glycerin and sodium diclofenac until the film is formed and then dried. Drop the sodium tripoli phosphate solution until a crosslink reaction occurs, then dried. Transdermal films were made in six formulas using chitosan (2%), polyvinyl alcohol (8%) with a ratio of 30:70 adding sodium tripolyphosphate solution at 10 minutes crosslink time (F1) and 20 minutes (F2), 50:50 crosslink time 10 minutes (F3) and 20 minutes (F4), 70:30 cross time 10 minutes (F5) and 20 minutes (F6). Evaluation of film character includes organoleptic observation, weight test, thickness, moisture content (%), interactions between ingredients, levels of active substances. Drug release was determined using Franz diffusion cells in phosphate buffer (pH7.4). All transdermal films meet the test requirements for uniformity in weight, thickness and moisture content. Penetration test in vitro film shows the formulation with 10 minutes crosslink time has cumulative percent and release flux is better than 20 minutes crosslink time. The release of dicofofen sodium transdermal film follows the release of a zero order erosion mechanism. FTIR examination showed no interaction between sodium diclofenac and excipients. Conclusion: Chitosan polymer, polyvinyl alcohol and sodium tripoli phosphate affect organoleptic properties and penetration through the skin. Transdermal film making with a 10 minute crosslink time results in a better release profile than a 20 minute crosslink time. Keywords: diclofenac sodium, chitosan, polyvinyl alcohol, sodium tripoli phosphate, glycerin, release kinetics.